Optimization of bacteriorhodopsin production by halostagnicola larsenii IBS (MCC 2956) (Funded Research Work) - PRADNYA P. KANEKAR; SNEHAL O. KULKARNI (International Journal of Pharma and Bio Sciences, 2017)
Haloarchaea are salt loving microorganisms isolated from saline environments including ancient salt deposits and rock salt. A few haloarchaeal species have been reported to produce bacteriorhodopsin (BR) which works as a light driven proton pump. A haloarchaeal strain Halostagnicola larsenii IBS (MCC 2956) isolated from commercial Indian black salt (IBS) sample was employed for optimization of BR production. The organism produced 0.288 g l-1 BR under optimum conditions as 3.42 M NaCl, pH 7-8, incubation temperature of 45 °C and incubation period of 9 days. The present report appears to be the first report on optimization of BR production using Halostagnicola larsenii IBS strain.